(untitled) (Ibrahim Medical College Journal, 2016)
Chronic kidney disease (CKD) with diabetes mellitus is one of the most common and major public health problems globally. In Bangladesh, several studies indicate an increasing prevalence of diabetes though very few studies are available on CKD. For CKD, diagnostic method, criteria or cutoffs still remained undecided. This study aimed to determine the prevalence of CKD among the hospitalized patients and to compare the diagnostic approach practiced in the hospital. Methods: All patients admitted to the Department of Nephrology at BIRDEM from May 1 to July 31, 2012 were selected for investigation. An almost equal number of patients were also selected from other units of Medicine. The information included were age, sex, social class, blood pressure, height, weight, blood glucose, creatinine, triglycerides, total cholesterol, high-density lipoproteins and electrolytes. The CKDcreat was diagnosed based on creatinine (>1.2mg/dl) and the CKDgfr based on estimated GFR (<60 ml/min/1.73m2) following Kidney Disease Outcomes Quality Initiative (K/DOQI) guideline. The comparisons of characteristics were made between CKDcreat and non- CKDcreat (? 1.2 vs.>1.2 mg/dl) groups. Similar comparisons were also made between CKDgfr and non-CKDgfr (>60 vs. ? 60 ml/min/1.732) groups. Results: A total of 4172 patients got admitted in the study period of 90 days; and 442 patients (m / f = 256 / 186) were investigated. Of the total (n=4172), 241 (5.8%) had CKDcreat and 272 (6.5%) had CKDgfr. Of the investigated 442 patients, 241 (54.5%) had CKDcreat and 272 (61.5%) had CKDgfr. The differences of characteristics between CKDcreat and non-CKDcreat groups were almost similar to the differences between CKDgfr and non-CKDgfr groups. Higher age, higher social class and higher blood pressure showed significant (p<0.001) and similar associations with both CKDcreat and CKDgfr. Interestingly, if the cut-off of eGFR is taken at <90 ml/min/1.732, as suggested by K/DOQI, the prevalence of CKDgfr increases to 86.7%. This indicates a wide variation (32.2%) between the two criteria (CKDcreat: creat >1.2 mg/dl and CKDgfr: <90 ml/min/1.732). Thus, a large proportion remained either under- or over-diagnosed depending on the criterion used. Conclusion: The prevalence of CKD among the hospitalized patients was found not negligible. The comparisons of two diagnostic criteria did differ and eGFR (K/DOQI) could detect higher proportion of CKD, which might be an over-diagnosis. Further study taking microalbuminuria, gross proteinuria, albumin-creatinine ratio and cystatin C may validate the method for the diagnostic accuracy of CKD, which my help assessing the prevalence of CKD accurately. Ibrahim Med. Coll. J. 2014; 8(2): 50-55